Pengaruh Aplikasi Wordwall terhadap Hasil Penggunaan Tanda Baca Titik dan Koma pada Teks Narasi Siswa Kelas 4 di Sekolah Dasar - Elvinda Putri Syafa'ah; Nanang Khoirul Umam (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
Writing skills are an important ability for students because they allow them to convey ideas or messages through writing. Grammar in writing is regulated by the General Guidelines for Indonesian Spelling (PUEBI). However, in practice, many students still do not understand these rules. As a result, writing errors often occur, especially in the use of commas and periods. That is why this research examines whether the wordwall application affects students' punctuation skills of periods and commas in writing narrative texts. This research was conducted in the 2023-2024 academic year at SDN 242 Bungah Gresik. This research is quantitative research using quasi-experimental methods. The population in this study was all class IV students at SDN 242 Bungah, totaling 32 students. The sample in this study used 2 classes, namely class IV A as the control class which applied conventional learning. Meanwhile, class IV B is an experimental class by implementing the wordwall application. The results of the study used the Man-Whitney test with a Sig (2-tailed) value of 0.001 < α (0.05), indicating that there were significant differences in learning outcomes between the experimental class and the control class.